Konflik Batin Dalam Novel Padang Bulan Karya Andrea Hirata Dan Implementasinya Sebagai Bahan Ajar Di Smp Muhammadiyah 10 Surakarta - Nofatagraha, Canggih Angga, Dra. Main, Sufanti M. Hum (2017)
This research explains the internal conflict in the novel 'Padang Bulan' written by Andrea Hirata and its plementation as a teaching material in SMP Muhammadiyah 10 Surakarta. Subject of the research is the internal conflict in the novel 'Padang Bulan' written by Andrea Hirata. This research used a strategy with a descriptive qualitative approach. The purposes of the research are: (1) to describe the structure which constructs the novel 'Padang Bulan' written byà Andrea Hirata, (2) to describe the internal conflict in the novel 'Padang Bulan' written by Andrea Hirata, (3) to describe the implementation of the research results in the literary learning in SMP Muhammadiyah 10 Surakarta. The data are in the forms of words, phrases, sentences, and discourses of the novel 'Padang Bulan' written by Andrea Hirata as a literary teaching material. The technique of data ollection: (a) the heuristic technique and the hermeneutic technique, (b) the interactive technique. The triangulation of theory was used to test the validity of data. Meanwhile, the esults of this research are as follows: (1) It was found the approach-approach conflict which occurs if there are two positive motives (2) It was found the approach-avoidance conflict which occurs if in the same time, there are two opposite motives on an object (3) It was found the voidance-avoidance conflict which occurs if in the same time, there are two negative motives, so, hesitation occurs which is possible to create an another negative motive. The results of this research were made as a teaching material of teen novel in SMP (junior high school), especially the 8th grade of first semester of Basic Competence (KD) 7.2. Making a Synopsis of Indonesian Teen Novel.Keywords: Novel Structure, Internal Conflict.